PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI PUSKESMAS GARUDA KECAMATAN ANDIR KOTA BANDUNG - Hari Mulyana; Suryanto Suryanto; Asep Iwa Hidayat (Journal Publicuho, 2023)
This study aims to examine the influence of motivation and work environment on employee performance in Puskesmas Garuda, Andir District, Bandung City. The research sample consisted of 58 employees of Puskesmas Garuda selected randomly. Data were collected using questionnaires that measured the variables of work motivation, work environment, and employee performance. Path analysis was employed to analyze the relationships among these variables. The results of the study indicate that work motivation and work environment have a significant influence on employee performance in Puskesmas Garuda. The path analysis reveals that work motivation has a significant positive effect on employee performance (path coefficient = 0.55, p < 0.05), while the work environment also has a significant positive influence on employee performance (path coefficient = 0.42, p < 0.05). These findings suggest that effective management of work motivation and work environment can enhance employee performance in Puskesmas Garuda. Management needs to pay sufficient attention to employee work motivation by creating a conducive work environment and providing appropriate support. Factors such as job satisfaction, achievement, recognition, supervisor support, teamwork, and clear work policies need to be considered in improving employee performance.